3.1.2-eg - Example Let f (x) = 3x2 − 1 . Use the...

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: Example Let f (x) = 3x2 − 1 . Use the definition of the derivative to find f (2) = lim f (2 + h) − f (2) h h→0 , (1) and then write the equation of the tangent line to the curve y = f (x) at the point (2, f (2)). Solution: Making the substitution f (2 + h) = 3(2 + h)2 − 1 into (1), it follows that f (2) = = = = = = (3(2 + h)2 − 1) − (3 · 22 − 1) lim h→0 h [3 (4 + 4h + h2 ) − 1] − (3 · 4 − 1) lim h→0 h 12 + 12h + 3h2 − 1 − 11 lim h→0 h 12h + 3h2 lim h→0 h h(12 + 3h) lim h→0 h lim 12 + 3h h→0 = 12. Thus the slope of the tangent line to the curve y = f (x) at the point (2, f (2)) is f (2) = 12. Using the point-slope formula of the line through (2, f (2)) = (2, 11) with slope f (2) = 12, y − f (2) = f (2)(x − 2) or, y − 11 = 12(x − 2), so the equation of the tangent line to the curve through the point (2, f (2)) is y = 11 + 12(x − 2). ...
View Full Document

This note was uploaded on 04/02/2012 for the course MTH 132 taught by Professor Kihyunhyun during the Fall '10 term at Michigan State University.

Ask a homework question - tutors are online